2023
DOI: 10.1021/acscentsci.2c01169
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Cascades toward Iminosugar Scaffolds Reveal Promiscuous Activity of Shikimate Dehydrogenases

Abstract: Iminosugar scaffolds are highly sought-after pharmaceutical targets, but their chemical synthesis is lengthy and can suffer from poor scalability and purification. Here we report protecting-group-free chemoenzymatic and biocatalytic cascades to synthesize iminosugars from sugar-derived aminopolyols in two steps. Using galactose oxidase variant F 2 followed by a chemical or enzymatic reduction provided an efficient one-pot route to these targets, with product formation >70%. Key to success of this strategy was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
6
0
2
Order By: Relevance
“…78 To date, the processing of shikimate into reduced and dehydrated cyclohexanes and cyclohexenes are the known routes to repurpose shikimate into natural product scaffolds, however recent investigations have demonstrated the flexibility of shikimate dehydrogenases in the biocatalytic synthesis of iminosugars. 79…”
Section: Shikimic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…78 To date, the processing of shikimate into reduced and dehydrated cyclohexanes and cyclohexenes are the known routes to repurpose shikimate into natural product scaffolds, however recent investigations have demonstrated the flexibility of shikimate dehydrogenases in the biocatalytic synthesis of iminosugars. 79…”
Section: Shikimic Acidmentioning
confidence: 99%
“…78 To date, the processing of shikimate into reduced and dehydrated cyclohexanes and cyclohexenes are the known routes to repurpose shikimate into natural product scaffolds, however recent investigations have demonstrated the exibility of shikimate dehydrogenases in the biocatalytic synthesis of iminosugars. 79 Shikimate itself is rarely directly incorporated into natural product scaffolds, with few notable exceptions such as the chlorogenic acids found in plants, as discussed in Section 3 (Fig. 5).…”
Section: Reviewmentioning
confidence: 99%
“…[30] Recently, AroE was postulated to reduce C=N bonds in iminosugar imines and was successfully combined with galactose oxidase to access imino sugar scaffolds from aminopolyols (Scheme 3B). [31] However, given the possibility for an Amadori rearrangement of the α-hydroxy-imine to an α-amino-ketone, it cannot be ruled out that the enzyme actually reduced a C=O bond. [31]…”
Section: Metabolism As a Source Of Catalytically Versatile Reductasesmentioning
confidence: 99%
“…[31] However, given the possibility for an Amadori rearrangement of the α-hydroxy-imine to an α-amino-ketone, it cannot be ruled out that the enzyme actually reduced a C=O bond. [31]…”
Section: Metabolism As a Source Of Catalytically Versatile Reductasesmentioning
confidence: 99%
“…In a one-pot reaction, Swanson et al showed that the galactose oxidase F 2 variant could catalyse the primary oxidation of unprotected aminopolyols 25, followed by a chemical reduction step for the preparation of various iminosugars 26 (Scheme 4d). [13] The intermediate 27 leading to the iminosugars with a deoxy-ribo or arabino configuration could be reduced by Shikimate dehydrogenases, possibly via an Amadori rearrangement, and subsequent enzyme-catalysed asymmetric ketone reduction of the α-amino carbonyl moiety. The GOase variants F 2 and M 3-5 have furthermore been used for the enzyme-triggered formation of non-sugar compounds, such as lactams 28, 29, and 30 (Scheme 4e).…”
Section: Enzyme-triggered Reactionsmentioning
confidence: 99%